Impact of the COVID-19 pandemic on agricultural exports - Ben-xi LIN; Yu Yvette ZHANG (Journal of Integrative Agriculture, 2020)
The COVID-19 outbreak has shocked the world's economies in the year of 2020. As this pandemic spreads around the globe, many experts feared that the global food supplies might start running short, especially if supply chains were disrupted. COVID-19 also added to the uncertainty of the business operation. Therefore, it is critical to understand how COVID-19 pandemic affected global food supply and market. In this study, we investigate the impact of COVID-19 on agricultural export companies in China using a unique firm-level survey data. We found that although on average agricultural businesses experienced declines in the exports, exports of some agricultural products especially grain and oil held strong and even increased, implying the essential demand for staple food during the pandemic. Not surprisingly, exports of medicinal herb also increased significantly during the pandemic. However, exports of goods such as edible fungus and horticultural products sharply decreased. Our results also showed that in general, impact of COVID-19 on smaller firms was more severe than that on larger firms. The results of this study can provide useful guidance and implications for agricultural businesses and policy makers on their COVID-19 mitigation efforts to navigate this global pandemic.